Komunikasi Rasulullah dalam Rumah Tangga - Resna Wahyuni; Ferry Darmawan (UNISBA Press, 2024)
Abstract. In the household, a lack of good communication is one of the triggers for problems. In this research, the author will discuss in more depth the discourse in the hadith of the Prophet as contained in the book